Implicaç\~oes do mecanismo da OCDE de conduta empresarial responsável sobre a governança e o modo de atuaç\~ao das EMNs - Cássio Garcia Ribeiro; Edmundo Inacio Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This report proposes to present and analyze the impacts of the set of standards and recommendations present in the Guidelines for Multinational Companies (OECD, 2011). This document represents the main initiative carried out by a multilateral organization, with the objective of guiding the actions of multinational companies (MNCs) in host countries. This is an extremely relevant topic, since several academic researches demonstrate that in addition to the positive effects provided by MNCs to host countries, foreign direct investment (FDI) can also bring harmful results to such countries. The Brazilian government adhered to the Guidelines in 1997 and has since made efforts to adapt to the content of this OECD instrument geared towards MNCs. The methodology adopted in this report was based on: i) literature review that addressed the themes of MNCs; ii) documentary research based on OECD reports and documents on the Guidelines and iii) mapping and tabulation of the results of all allegations of non-compliance received by the Brazilian National Contact Point (PCN), from 2003 to 2018. The evidence of this study indicate that the Guidelines have enormous potential, functioning as an instrument that brings publicity to the possible damage caused by MNCs. However, there are also points to be improved. From this study it was identified: i) that there are difficulties for an effective accountability of MNCs due to the damage caused to host countries by corporate misconduct; ii) the importance of implementing a mandatory peer review system, which would assess the opinions issued by the NCPs.
Keywords: F51; F53; 330; guidelines; MNCs; PCN; impacts